Blood loss : a love story of AIDS, activism, and art - Lane, Keiko, 1974- (Duke University Press, 2024)
"In 1991, 16-year-old activist Keiko Lane joined the Los Angeles chapters of Queer Nation and ACT UP. They protested against legislation aimed at dismantling rights for LGBTQ people, people living with HIV, and immigrants, while fighting for needle exchange programs, reproductive justice, safer sex education, hospice funding, and the right to die with dignity. At the same time, they were a queer chosen family of friends and lovers who took care of one another in sickness and in health. Sometimes they helped each other die. By the time Lane turned 22, most of them had died of AIDS. In her evocative memoir, Lane weaves together the love stories and afterlives of queer resistance and survival, against the landscape of the Rodney King Rebellion, the movement for queer rights, and the censorship of queer artists and sexualities. Lane interrogates the social construction of power against and in queer communities of color, and the recovery of sexual agency in the midst and aftermath of violence. Luminous and powerfully moving, Blood Loss explores survival after those we love have died"-- Provided by publisher.
Keywords: Lane, Keiko, -- 1974-; AIDS activists -- California -- Los Angeles -- Biography.; LGBT activism -- California -- Los Angeles.; Art -- Political aspects -- California -- Los Angeles.; SOCIAL SCIENCE / LGBTQ+ Studies / Gay Studies; Autobiography; autobiographies (literary genre); Autobiographies.